Strategi Guru bahasa Arab dalam Meningkatkan Kemampuan Berbicara Bahasa Arab siswa Kelas VII di SMPIT Daarussalaam Sangatta Utara - Lailatul Aisyah; Rusmiati Indrayani; Farida Catur Wahyu Anggriyani (Civiliza Publishing, Indonesia., 2026)
This study aims to determine the Arabic speaking skills of seventh-grade students at SMPIT Daarussalaam and the strategies used by Arabic teachers to improve their Arabic speaking skills. This is a descriptive qualitative study with a phenomenological approach. This research is motivated by the difficulties junior high school students face in speaking Arabic due to limited vocabulary, limited practice, and low motivation, despite Arabic's importance as the language of the Quran and Islamic teachings. The study was conducted at SMPIT Daarussalaam in North Sangatta, East Kutai, from August 18 to October 15, 2025, with data sourced from the Arabic teacher, two students, and school documents. Data collection was conducted through observation, in-depth interviews, and document review, then analyzed using the Miles and Huberman model. The results indicate that students' speaking skills were initially low, but improved significantly through the integrated strategies implemented by the teachers. The main strategy includes the Mustaqilli method, which integrates structured grammar and morphology, daily recitation, dictation practice, group discussions, oral feedback, and the use of Smart TV. This approach has proven effective in encouraging active practice and building motivation based on Islamic values, aligning with communicative theory, behaviorism, and constructivism, and providing practical guidance for teachers and schools in holistic Arabic language learning.